2021
DOI: 10.22541/au.161823007.77608859/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leopard (Panthera pardus) occupancy in the Chure range of Nepal.

Abstract: Conservation of large carnivores like leopards requires large and interconnected habitats. Despite the wide geographic range of the leopard globally, only 17% of their habitat is within protected areas. In Nepal, leopards are distributed widely across the country but their status is not adequately studied which compromised the necessary conservation attention for the species. This study carried out sign-based occupancy survey across the Chure (the Himalayan foothills) range (~19,000 km2) to understand the habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…This result underscores the significance of integrating RAIs of potential prey species into modelling Leopard occupancy. Lamichhane et al (2021) showed that the presence of the Wild Boar is a strong predictor of Leopard occupancy in a forested mountain range in Nepal. In several study areas in Asia, the Wild Boar constitutes a major proportion of the Leopard's diet (Sharbafi et al 2016;Kandel et al 2020), especially when other prey species are depleted (Ghoddousi et al 2017).…”
Section: Leopard Occupancymentioning
confidence: 99%
“…This result underscores the significance of integrating RAIs of potential prey species into modelling Leopard occupancy. Lamichhane et al (2021) showed that the presence of the Wild Boar is a strong predictor of Leopard occupancy in a forested mountain range in Nepal. In several study areas in Asia, the Wild Boar constitutes a major proportion of the Leopard's diet (Sharbafi et al 2016;Kandel et al 2020), especially when other prey species are depleted (Ghoddousi et al 2017).…”
Section: Leopard Occupancymentioning
confidence: 99%
“…Thapa and Kelly (2016, 2017) carried out first detail systematic survey of wildlife in the Nepal's forgotten tiger land‐Churia‐ within the protected areas. Ecological relevance of Churia habitat for tiger conservation (Thapa & Kelly, 2017) contributed to nationwide survey of Churia physiographic zone for faunal assessment (Lamichhane et al, 2021). It is often argued that climate change and human disturbances are anticipated to alter both wildlife distributions and their movement patterns, increasing the risk of defaunation and habitat destruction for many endangered species and ecosystem (Gaynor et al, 2018; Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Nepal, Leopards (Panthera pardus) are common in the foothills of the Nepalese Himalayas, though densely populated by human settlements (Nowell & Jackson, 1996). Studies showed the declining trend of the Leopard population in many parts of Africa and south Asia due to habitat loss and depletion of prey (Kumar, 2011;Thapa et al, 2021;Lamichhane et al, 2021). Leopard is common in the forests across the Himalayas and its food consists of wild prey species such as Himalayan goral (Naemorhedus goral), Barking deer or Northern red muntjac (Muntiacus vaginalis), Wild boar (Sus scrofa), Jungle fowl (Gallus gallus) and Langur (Semnopithecus sp.).…”
Section: Introductionmentioning
confidence: 99%